International Female Migration to Atlantic Canada through Internet Mediated MatchMaking Agencies - Brigham, Susan M.; Abidi, Catherine Baillie (Atlantis)

(untitled) (Mount Saint Vincent University, 2009)
In this paper we draw on post-colonial feminism in order to analyze the complex ways in which gender, race, class, nationality, and education affect women who have migrated to Atlantic Canada via the international Internet matchmaking industry. We discuss power which is a recurring theme identified in the data.